Exploring barriers for psychiatrists in discussing substance abuse with child and adolescent patients: a multiple goals approach. Issue 5 (3rd September 2018) - Wombacher, Kevin; Watterson, Tara C.; Scott, Allison M.; Harrington, Nancy Grant; Martin, Catherine A
ABSTRACT: Patients suffering from psychiatric illnesses, however, are often at increased risk for substance use disorders; therefore, it is important for practitioners to have effective conversations about substance use with these patients. Child and adolescent psychiatrists (CAPs), in particular, are in a unique position to identify early substance use and affect the trajectory of adolescents who are at increased risk for substance abuse. To better understand such communication between psychiatrists and their patients, we conducted 21 in-depth interviews with CAPs to explore what barriers exist to prevent or dissuade CAPs from discussing substance abuse with their patients. We found barriers to effective communication at the micro, meso, and macro levels within the ecology of the field of psychiatry. A multiple goals perspective allowed us to determine how these barriers affect communication choices. Findings from the study highlight the significant communication challenges faced by psychiatrists in this context.